Figure 9 from: Saarela JM, Sokoloff PC, Gillespie LJ, Bull RD, Bennett BA, Ponomarenko S (2020) Vascular plants of Victoria Island (Northwest Territories and Nunavut, Canada): a specimen-based study of an Arctic flora. PhytoKeys 141: 1-330. https://doi.org/10.3897/phytokeys.141.48810 - Saarela, Jeffery M.; Sokoloff, Paul C.; Gillespie, Lynn J.; Bull, Roger D.; Bennett, Bruce A.; Ponomarenko, Serguei (Zenodo, 2022)
Figure 9 AEquisetum arvense subsp. alpestre strobilus (left) and habit (right), Gillespie et al. 10109BEquisetum variegatum subsp. variegatum habit, Gillespie et al. 8499CCystopteris fragilis habit, Gillespie et al. 9990DDryopteris fragrans habit, Johansen Bay, 18 July 2008 EWoodsia glabella habit FWoodsia glabella habitat GTofieldia coccinea inflorescences, Kuujjua River, NT, 18 July 2010 HTofieldia coccinea habit, Gillespie et al. 9749. Photos A, C by L.J. Gillespie B, D, G by R.D. Bull H by J.M. Saarela and E, F by B.A. Bennett.